CYP2C19*2 status in patients with Stevens-Johnson syndrome and toxic epidermal necrolysis - Laska AJ; Han MJ; Lospinoso JA; Brown PJ; Beachkofsky TM (Dove Medical Press, 2017)
Amanda J Laska,1 Marie J Han,1 Josh A Lospinoso,2 Patrick J Brown,1 Thomas M Beachkofsky1 1Department of Dermatology, San Antonio Uniformed Services Health Education Consortium, San Antonio, TX, 2780th Military Intelligence Brigade, Ft Meade, MD, USA Purpose: Genetic polymorphisms have been linked to an increased predisposition to developing certain diseases. For example, patients of Han-Chinese descent carrying the HLA-B*1502 allele are at an increased risk of developing Stevens-Johnson syndrome and toxic epidermal necrolysis (SJS/TEN) if given carbamazepine. Given the complexity of in vivo drug metabolism, it is plausible that the activity of enzyme systems unrelated to specific drug metabolism may be important. Although multiple biomarkers have been identified in unique ethnic groups, there has yet to be a study investigating the presence of the slow metabolizing allele of CYP2C19, denoted CYP2C19*2, in diverse groups and the risk of developing SJS/TEN. Patients and methods: This study looked into the carrier status of CYP2C19*2, a poor metabolizing variant of CYP2C19, in patients diagnosed with SJS/TEN. We looked at its status in our series as a whole and when patients were divided by ethnicity. Genomic DNA was extracted from formalin-fixed paraffin-embedded tissue of patients with biopsy-proven SJS/TEN and real-time polymerase chain reaction was used to assess for the presence of CYP2C19*2. Results: CYP2C19*2 status was determined in 47 patients. Twenty-nine of these 47 patients had a single medication implicated as causing their disease, and eight of these patients were heterozygous or homozygous for CYP2C19*2. There was insufficient evidence to conclude that the presence of CYP2C19*2 is an independent predictor of risk for developing SJS/TEN in our series as a whole. This analysis also confirmed that the frequency of the CYP2C19*2 polymorphism within the different ethnicities in our series did not vary statistically from reported ethnic rates. Conclusion: Our study was unable to show a relationship between CYP2C19*2 status and predisposition toward SJS/TEN. We had a heterogeneous population, making it difficult to control for possible confounding factors. Keywords: drug reactions, drug metabolism, adverse events, dermatology